Financial Risk Management in The Face of Global Economic Uncertainty - La Jimu; Olyvia Rosalia; Firayani (Maneggio, 2025)
Global economic uncertainty marked by exchange rate fluctuations, changes in commodity prices, geopolitical crises, and international trade tensions poses significant challenges for multinational companies in maintaining financial stability and operational sustainability. This study aims to analyze the role of financial risk management strategies in strengthening corporate resilience against global market dynamics. Using a quantitative approach and regression analysis, the research examines the relationship between the implementation of strategies such as hedging, portfolio diversification, cash reserves, and debt management and corporate financial stability indicators. The findings show that financial risk management strategies have a positive and significant impact in facing market volatility, with the use of derivatives and liquidity management proving to be the most effective. The study also reveals implementation challenges, such as limited information and the complexity of cross-border regulations. These findings contribute to the global financial management literature and serve as a valuable reference for policymakers and business practitioners in designing adaptive and robust financial strategies amidst global uncertainty.